TINGKAT KEBERSIHAN GIGI DAN MULUT SISWA SD N 1 NYUH TEBEL MANGGIS KARANGASEM - I Nengah Dana; I Made Budi Artawa (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2023)
Age group of 12 is uses as a standard age to asses dental disease globally (global caries monitoring age) to be compared internationally. The purpose of this experiment is to know the level of oral hygiene of sixth grade students in SDN 1 Nyuh Tebel Kecamatan Manggis Kabupaten Karangasem 2018. This study is a descriptive with survey design. The population is all of sixth grade students (35 person). The data is primary which taken from direct examination. The results show that most student have debris value with moderate criteria (0,7-1,8) is 22 students (62,86%) and calculus with good criteria (0,0-0,6) is 17 students (48,57%). Based on sex, most of female have OHI-S in moderate criteria 14 students (77,78%) and there is no female has a good criteria for OHI-S. As the conclusion, debris index, calculus index, and OHI-S in moderate criteria most common found in female.